Magnetic field-induced absorbable surgical suture of core-sheath type and method for its production

CN122827740APending Publication Date: 2026-09-29NINGBO INST OF MATERIALS TECH & ENG CHINESE ACAD OF SCI
View PDF 6 Cites 0 Cited by

Patent Information

Application Number
CN202611053482.6
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2026-07-15
Publication Date
2026-09-29

AI Technical Summary

Technical Problem

[0006]本发明的主要目的在于克服现有磁性可吸收手术缝合线中磁性纳米粒子分布不可控、粒子随机分布导致磁响应效率低、裸露Fe3O4催化PGLA提前降解、粒子与基体界面结合弱、以及缝合线力学性能和磁热效率难以协同优化的技术缺陷,提供一种磁性粒子在皮层中呈轴向链状排列并向表面富集、在芯层中呈轴向链状排列并向皮层-芯层界面富集、磁性粒子/聚合物界面结合强度高、储存稳定性优异、同时具备磁各向异性力学增强和磁热效应可编程降解功能的皮芯型可吸收手术缝合线及其制备方法

Benefits of technology

(1)本发明将Fe3O4@SiO2-g-PGLA核壳接枝纳米粒子和Fe3O4@SiO2-g-PGA核壳纳米粒子引入PGLA/PGA皮芯型可吸收手术缝合线,通过SiO2壳层物理屏障抑制Fe3O4对PGLA和PGA的催化降解,显著提升缝合线的储存稳定性;通过PGLA接枝层提升Fe3O4@SiO2纳米粒子与PGLA基体的界面相容性,PGA接枝层提升Fe3O4@SiO2纳米粒子与PGA基体的界面相容性,显著降低相同磁响应行为下的Fe3O4@SiO2纳米粒子添加量,提升纺丝稳定性;

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN122827740A_ABST
    Figure CN122827740A_ABST
Patent Text Reader

Abstract

This invention discloses a magnetic field-induced core-and-skin absorbable surgical suture and its preparation method. The core-and-skin absorbable surgical suture comprises a skin layer and a core layer. The skin layer comprises polyethylene glycol (PEG) and Fe3O4@SiO2-g-PGA core-shell nanoparticles; the core layer comprises PEG and Fe3O4@SiO2-g-PGA core-shell nanoparticles. The core-and-skin absorbable surgical suture prepared by this invention can degrade rapidly on demand under the action of an alternating magnetic field, achieving spatiotemporal controllable adjustment of the postoperative degradation rate. It also possesses the potential for MRI visualization and tracking, providing a new solution for the clinical application of intelligent absorbable sutures.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] This invention belongs to the field of absorbable surgical suture technology, specifically relating to a magnetically induced core-skin type absorbable surgical suture and its preparation method. Background Technology

[0002] Absorbable surgical sutures are crucial medical devices widely used in surgical procedures. They degrade and are absorbed on their own after tissue healing, avoiding the need for secondary suture removal. Polyglycolic acid (PGA) and polyglycolic acid lactide (PGLA) are currently the most commonly used absorbable suture materials in clinical practice. PGA has high initial strength, but its degradation rate is relatively fast and its degradation products are highly acidic, easily causing tissue inflammation. PGLA's degradation rate can be adjusted through copolymerization, but its initial strength is lower than that of PGA.

[0003] In recent years, the introduction of magnetic nanoparticles into absorbable sutures to achieve magnetic resonance imaging (MRI) visualization and on-demand degradation control of the magnetocaloric effect has become a research hotspot. Patent application CN202210991560.2 discloses a magnetic composite fiber and its application in self-controlled degradation surgical sutures, which involves blending Fe3O4 with PGLA and spinning it, using an external alternating magnetic field to generate a magnetocaloric effect to accelerate degradation. However, this approach has the following technical drawbacks: (1) Exposed catalytic active sites on the Fe3O4 surface accelerate premature degradation of PGLA, resulting in poor suture storage stability; (2) Fe3O4 particles are randomly distributed in the fiber, leading to low magnetocaloric efficiency; (3) The lack of precise control over particle spatial distribution makes it difficult to synergistically optimize mechanical and magnetic response properties.

[0004] Previous studies have shown that applying a magnetic field during melt spinning can induce the migration of magnetic particles to the fiber surface (Buschbeck et al., 2017; DOI:10.4236 / MSCE.2017.512001). However, this study used non-degradable polypropylene and polyamide matrices, and the particles were Fe3O4@Ag, failing to address the catalytic degradation problem of absorbable polyesters, and also neglecting the dual control of particle axial alignment and surface enrichment. Furthermore, patent application CN202511254956.9 discloses a method for producing magnetic fiber fabrics. Fe3O4 is modified with silane and then in-situ compounded with polyamic acid to obtain a masterbatch; this masterbatch is further blended with polyamide and melt-spun to obtain magnetic fibers; subsequently, magnetic domains are activated by multi-level step magnetization using a 1.5~4.5T pulsed magnetic field. The resulting magnetic fabric possesses high magnetic induction intensity, excellent washability, long-lasting magnetic stability, and good wearing comfort. However, this patent does not induce the migration of magnetic particles to the fiber surface during the melt spinning stage. Patent application number CN201510416128.0 discloses a magnetic field-induced assisted spinning forming device and its production method for conductive / magnetic chemical fibers. The feature is that an electromagnetic coil is vertically connected to a spinneret, and the hollow part of the electromagnetic coil is aligned with the center of the spinneret. Under the action of the magnetic field of the electromagnetic coil, magnetic powders such as Fe3O4 in the polymer melt are arranged in the direction of the magnetic field lines to form microfibers or bead structures. The filaments are cooled and solidified to obtain the finished conductive / magnetic composite fiber. However, this patent does not solve the problem of catalytic degradation of absorbable polyester.

[0005] In addition, core-sheath composite fibers have also been reported in the field of sutures. Patent application CN202411063719.X discloses a drug / electro-synergistic antibacterial and healing-promoting suture. By adding micro / nano-electrocouple particles with different electrode potentials to the core-spinning polymer solution, a synergistic effect of continuous electrical stimulation and controlled drug release from the core layer is achieved through electrochemical reaction. Patent application CN202311250100.5 develops a multifunctional core-spinning surgical suture. It uses coaxial conjugate electrospinning technology to prepare a porous drug-loaded nanofiber functional coating layer as the skin layer, which wraps a biodegradable filament core yarn layer with excellent mechanical properties, simultaneously achieving excellent mechanical properties, controlled drug release, healing promotion, water retention, and antibacterial functions. Patent application CN202310842870.2 develops a drug-loaded nanofiber membrane / polylactic acid core-spinning suture. Polylactic acid filaments are used as the core layer to ensure mechanical properties, and polycaprolactone / polyglycolic acid nanofiber membranes are used as the skin layer. The degradation and drug release cycles are dynamically matched by adjusting the ratio of the two. However, existing core-skin sutures primarily focus on mechanical properties or drug release, with no reports of combining magnetic core-shell grafted particles with magnetic field induction technology for use in absorbable sutures. Therefore, developing an absorbable surgical suture that combines high initial strength, enhanced magnetic anisotropy, magnetocaloric programmable degradation, and excellent storage stability is of significant clinical importance. Summary of the Invention

[0006] The main objective of this invention is to overcome the technical defects of existing magnetic absorbable surgical sutures, such as uncontrollable distribution of magnetic nanoparticles, low magnetic response efficiency due to random particle distribution, premature degradation of PGLA catalyzed by exposed Fe3O4, weak bonding between particles and the matrix interface, and difficulty in synergistically optimizing the mechanical properties and magnetocaloric efficiency of the suture. The invention provides a core-shell type absorbable surgical suture and its preparation method, in which magnetic particles are arranged in an axial chain in the skin layer and enriched on the surface, arranged in an axial chain in the core layer and enriched at the skin-core interface, exhibiting high bonding strength at the magnetic particle / polymer interface, excellent storage stability, and simultaneously possessing magnetic anisotropic mechanical enhancement and programmable degradation functions based on magnetocaloric effects.

[0007] To achieve the aforementioned objectives, the technical solution adopted by this invention includes: This invention provides a magnetically induced core-shell absorbable surgical suture, comprising a skin layer and a core layer. The skin layer comprises poly(glycolic acid) lactide (PGLA) and Fe3O4@SiO2-g-PGLA core-shell nanoparticles. The Fe3O4@SiO2-g-PGLA core-shell nanoparticles comprise Fe3O4 as the core, a SiO2 shell as the intermediate shell, and poly(glycolic acid) lactide as the surface graft layer. The surface graft layer is grafted onto the surface of the SiO2 shell through ring-opening polymerization or chemical coupling. The Fe3O4@SiO2-g-PGLA core-shell nanoparticles are arranged in a chain-like orientation along the suture axis in the skin layer, and are enriched on the skin layer surface, with their content gradually increasing in the direction away from the core layer. The core layer comprises polyglycolic acid (PGA) and Fe3O4@SiO2-g-PGA core-shell nanoparticles; wherein the Fe3O4@SiO2-g-PGA core-shell nanoparticles comprise Fe3O4 as the core, a SiO2 shell as the intermediate shell, and PGA as the surface graft layer. The surface graft layer is grafted onto the surface of the SiO2 shell by ring-opening polymerization or chemical coupling. The Fe3O4@SiO2-g-PGA core-shell nanoparticles are arranged in a chain-like orientation along the surgical suture axis in the core layer, and are enriched at the interface between the skin and the core layer, with the content gradually increasing in the core layer in the direction away from the core layer.

[0008] This invention also provides a method for preparing the aforementioned magnetically induced core-and-skin absorbable surgical suture, comprising: PGLA was melt-blended and granulated with Fe3O4@SiO2-g-PGLA core-shell nanoparticles to obtain a skin layer blend. PGA and Fe3O4@SiO2-g-PGA core-shell nanoparticles were melt-blended and granulated to obtain the core layer blend; The sheath blend and core blend are coaxially melt-spun; after extrusion from a coaxial spinneret, a magnetic field generator is placed below the spinneret. The applied directional gradient magnetic field causes Fe3O4@SiO2-g-PGLA core-shell nanoparticles and Fe3O4@SiO2-g-PGA core-shell nanoparticles to rotate along the fiber axis under the action of the magnetic field, forming a chain-like arrangement, and migrating and enriching towards the sheath surface and towards the interface between the sheath and the core, respectively, with the content gradually increasing in the direction away from the core. Subsequently, the fibers are rapidly cooled in a cold water bath to obtain nascent fibers; and the nascent fibers are stretched and heat-set to obtain magnetically induced sheath-core type absorbable surgical sutures.

[0009] Compared with the prior art, the beneficial effects of the present invention are as follows: (1) In this invention, Fe3O4@SiO2-g-PGLA core-shell grafted nanoparticles and Fe3O4@SiO2-g-PGA core-shell nanoparticles are introduced into PGLA / PGA core-shell type absorbable surgical sutures. The physical barrier of the SiO2 shell inhibits the catalytic degradation of PGLA and PGA by Fe3O4, which significantly improves the storage stability of the sutures. The PGLA grafting layer improves the interfacial compatibility between Fe3O4@SiO2 nanoparticles and the PGLA matrix, and the PGA grafting layer improves the interfacial compatibility between Fe3O4@SiO2 nanoparticles and the PGA matrix. This significantly reduces the amount of Fe3O4@SiO2 nanoparticles added under the same magnetic response behavior and improves the spinning stability. (2) In this invention, after the spinning melt is extruded from the coaxial spinneret, a magnetic field generating device is set below the spinneret. This allows Fe3O4@SiO2-g-PGLA core-shell nanoparticles and Fe3O4@SiO2-g-PGA core-shell nanoparticles to rotate along the fiber axis under the action of the magnetic field and form a chain-like arrangement. They migrate and accumulate to the surface of the cortex and to the interface between the cortex and the core, respectively, and the content gradually increases in the direction away from the core. The above dual spatial distribution control makes the magnetic anisotropy ratio reach 1.5~3.0. At the same time, the magnetocaloric efficiency is significantly improved compared with the randomly distributed control sample, and magnetocaloric programmable degradation can be achieved. (3) The present invention provides high initial strength through the PGA core layer. The Fe3O4@SiO2-g-PGA nanoparticles in the core layer are magnetically induced to axially align, which further promotes the orientation of PGA molecular chains; the Fe3O4@SiO2-g-PGLA nanoparticles in the skin layer are magnetically induced to axially align, which further promotes the orientation of PGLA molecular chains; the two work together to enhance the mechanical and magnetic response properties of the PGLA / PGA skin-core type absorbable surgical suture. (5) The core-skin type surgical suture prepared by the present invention can be accelerated to degrade as needed under the action of alternating magnetic field, realizing spatiotemporal controllable adjustment of the postoperative degradation rate, and at the same time has the potential for MRI visualization tracking, providing a new solution for the clinical application of intelligent absorbable sutures. Attached Figure Description

[0010] To more clearly illustrate the technical solutions in the embodiments of this application or the prior art, the drawings used in the description of the embodiments or the prior art will be briefly introduced below. Obviously, the drawings described below are only some embodiments recorded in this application. For those skilled in the art, other drawings can be obtained based on these drawings without creative effort.

[0011] Figure 1 These are electron microscope images of the Fe3O4@SiO2 core-shell nanoparticles prepared in this invention; Figure 2This is a stress-strain curve of the surgical suture prepared in Example 1 of the present invention before and after 6 months of storage. Detailed Implementation

[0012] In view of the deficiencies of the prior art, the inventors of this case, through long-term research and extensive practice, have proposed the technical solution of this invention. The technical solution of this invention will be clearly and completely described below. Obviously, the described embodiments are only some, not all, of the embodiments of this invention. All other embodiments obtained by those skilled in the art based on the embodiments of this invention without creative effort are within the scope of protection of this invention.

[0013] Specifically, as one aspect of the technical solution of the present invention, a magnetic field-induced skin-core type absorbable surgical suture includes a skin layer and a core layer. The skin layer includes poly(glycolic acid) lactide (PGLA) and Fe3O4@SiO2-g-PGLA core-shell nanoparticles. The Fe3O4@SiO2-g-PGLA core-shell nanoparticles include Fe3O4 as the core, SiO2 as the intermediate shell layer, and poly(glycolic acid) lactide as the surface graft layer. The surface graft layer is grafted onto the surface of the SiO2 shell layer by ring-opening polymerization or chemical coupling. The Fe3O4@SiO2-g-PGLA core-shell nanoparticles are arranged in a chain-like orientation along the axial direction of the surgical suture in the skin layer and are enriched towards the surface of the skin layer. The content of the nanoparticles gradually increases in the skin layer away from the core layer. The core layer comprises polyglycolic acid (PGA) and Fe3O4@SiO2-g-PGA core-shell nanoparticles; wherein the Fe3O4@SiO2-g-PGA core-shell nanoparticles comprise Fe3O4 as the core, a SiO2 shell as the intermediate shell, and PGA as the surface graft layer. The surface graft layer is grafted onto the surface of the SiO2 shell through ring-opening polymerization or chemical coupling. The Fe3O4@SiO2-g-PGA core-shell nanoparticles are arranged in a chain-like orientation along the surgical suture axis in the core layer, and are enriched at the interface between the skin layer and the core layer, with the content gradually increasing in the core layer in the direction away from the core layer. In some preferred embodiments, the mass ratio of PGLA to Fe3O4@SiO2-g-PGLA core-shell nanoparticles in the skin layer is 100:1~10.

[0014] Furthermore, the mass ratio of PGLA to Fe3O4@SiO2-g-PGLA core-shell nanoparticles in the cortex is 100:3~8.

[0015] Furthermore, the mass ratio of PGLA to Fe3O4@SiO2-g-PGLA core-shell nanoparticles in the cortex is 100:4~6.

[0016] In some preferred embodiments, the mass ratio of PGA to Fe3O4@SiO2-g-PGA core-shell nanoparticles in the core layer is 100:0.1~3.

[0017] Furthermore, the mass ratio of PGA to Fe3O4@SiO2-g-PGA core-shell nanoparticles in the core layer is 100:0.6~2.2.

[0018] Furthermore, the mass ratio of PGA to Fe3O4@SiO2-g-PGA core-shell nanoparticles in the core layer is 100:1.0~1.4.

[0019] In some preferred embodiments, the content of the skin layer in the core-type absorbable surgical suture is 25-60 wt%.

[0020] Furthermore, the content of the dermis in the core-type absorbable surgical suture is 35~50wt%.

[0021] Furthermore, the content of the dermis in the core-type absorbable surgical suture is 40-45 wt%.

[0022] In some preferred embodiments, the weight-average molecular weight of the PGLA is 80,000 to 250,000.

[0023] Furthermore, the weight-average molecular weight of the PGLA is 140,000 to 200,000.

[0024] Furthermore, the weight-average molecular weight of the PGLA is 160,000 to 180,000.

[0025] In some preferred embodiments, the molar content of LA (lactic acid monomer) in the PGLA is 5-15%.

[0026] Furthermore, the molar content of LA in the PGLA is 7-13%.

[0027] Furthermore, the molar content of LA in the PGLA is 9-11%.

[0028] In some preferred embodiments, the weight-average molecular weight of the PGA is 100,000 to 280,000.

[0029] Furthermore, the weight-average molecular weight of the PGA is 160,000 to 220,000.

[0030] Furthermore, the weight-average molecular weight of the PGA is 170,000 to 190,000.

[0031] In some preferred embodiments, the Fe3O4 core in the Fe3O4@SiO2-g-PGLA core-shell nanoparticles has a particle size of 20~50 nm.

[0032] Furthermore, the Fe3O4 core in the Fe3O4@SiO2-g-PGLA core-shell nanoparticles has a particle size of 25~40 nm.

[0033] Furthermore, the Fe3O4 core in the Fe3O4@SiO2-g-PGLA core-shell nanoparticles has a particle size of 28~35 nm.

[0034] In some preferred embodiments, the thickness of the SiO2 shell in the Fe3O4@SiO2-g-PGLA core-shell nanoparticles is 5~15 nm.

[0035] Furthermore, the thickness of the SiO2 shell in the Fe3O4@SiO2-g-PGLA core-shell nanoparticles is 7~12 nm.

[0036] Furthermore, the thickness of the SiO2 shell in the Fe3O4@SiO2-g-PGLA core-shell nanoparticles is 8~10 nm.

[0037] In some preferred embodiments, the grafting rate of poly(lactic acid) as a surface grafting layer in the Fe3O4@SiO2-g-PGLA core-shell nanoparticles is 10~30wt%.

[0038] Furthermore, the grafting rate of poly(lactic acid) as the surface grafting layer in the Fe3O4@SiO2-g-PGLA core-shell nanoparticles is 15~25wt%.

[0039] Furthermore, the grafting rate of poly(lactic acid) as the surface grafting layer in the Fe3O4@SiO2-g-PGLA core-shell nanoparticles is 18~22wt%.

[0040] In some preferred embodiments, the Fe3O4 core in the Fe3O4@SiO2-g-PGA core-shell nanoparticles has a particle size of 20~50 nm.

[0041] Furthermore, the Fe3O4 core in the Fe3O4@SiO2-g-PGA core-shell nanoparticles has a particle size of 25~40 nm.

[0042] Furthermore, the Fe3O4 core in the Fe3O4@SiO2-g-PGA core-shell nanoparticles has a particle size of 28~35 nm.

[0043] In some preferred embodiments, the thickness of the SiO2 shell in the Fe3O4@SiO2-g-PGA core-shell nanoparticles is 5~15 nm.

[0044] Furthermore, the thickness of the SiO2 shell in the Fe3O4@SiO2-g-PGA core-shell nanoparticles is 7~12 nm.

[0045] Furthermore, the thickness of the SiO2 shell in the Fe3O4@SiO2-g-PGA core-shell nanoparticles is 8~10 nm.

[0046] In some preferred embodiments, the grafting rate of polyglycolic acid, which serves as the surface grafting layer in the Fe3O4@SiO2-g-PGA core-shell nanoparticles, is 10~30wt%.

[0047] Furthermore, the grafting rate of polyglycolic acid, which serves as the surface grafting layer in the Fe3O4@SiO2-g-PGA core-shell nanoparticles, is 15~25wt%.

[0048] Furthermore, the grafting rate of polyglycolic acid, which serves as the surface grafting layer, in the Fe3O4@SiO2-g-PGA core-shell nanoparticles is 18~22wt%.

[0049] In some preferred embodiments, the suture has a higher magnetic susceptibility along the axial direction than that perpendicular to the axial direction, with a magnetic anisotropy ratio of 1.5 to 3.0:1.

[0050] Furthermore, the susceptibility of the surgical suture along the axial direction is higher than that perpendicular to the axial direction, and the magnetic anisotropy ratio is 2.0~3.0 : 1.

[0051] Furthermore, the susceptibility of the surgical suture along the axial direction is higher than that perpendicular to the axial direction, and the magnetic anisotropy ratio is 2.7~3.0 : 1.

[0052] In some preferred embodiments, the preparation method of the Fe3O4@SiO2-g-PGLA core-shell nanoparticles includes: Fe3O4 nanoparticles were prepared by a solvothermal method, and then SiO2 was coated on the surface of the Fe3O4 nanoparticles by the Stöber method to obtain Fe3O4@SiO2 nanoparticles. Furthermore, the Fe3O4@SiO2 nanoparticles are subjected to surface amination treatment to obtain amination nanoparticles, and then PGLA is grafted onto the surface of the amination nanoparticles by ring-opening polymerization to obtain Fe3O4@SiO2-g-PGLA core-shell nanoparticles.

[0053] In some preferred embodiments, the preparation method of the Fe3O4@SiO2-g-PGLA core-shell nanoparticles includes: (1) FeCl3·6H2O was mixed with NaAc and PEG in ethylene glycol, and Fe3O4 nanoparticles were prepared by solvothermal method. The molar ratio of FeCl3·6H2O to NaAc was 1:2~4, and the mass-volume ratio of PEG (molecular weight 4000~6000) to ethylene glycol was 1g:50~100mL. The reaction pressure was autogenous pressure (closed high pressure vessel), the reaction temperature was 180~220℃, and the reaction time was 8~12 h. After the reaction, the nanoparticles were washed 2~3 times with anhydrous ethanol and deionized water, and vacuum dried at 40~60℃ for 6~12 h. The particle size of the obtained Fe3O4 nanoparticles was about 20~50 nm. (2) Fe3O4 nanoparticles were ultrasonically dispersed in an ethanol / water mixture (volume ratio 4:1), the pH was adjusted to alkaline (pH=8~10), TEOS was slowly added dropwise, and after washing, the Fe3O4@SiO2 core-shell nanoparticles were obtained by vacuum drying. The pH was 8~10, the dropping rate was about 0.05~0.2 mL / min, the reaction time was 12~24 h, the drying temperature was 40~60℃, the drying time was 6~12 h, and the particle size of the obtained Fe3O4@SiO2 core-shell nanoparticles was about 25~65 nm. (3) Disperse Fe3O4@SiO2 nanoparticles in anhydrous ethanol, with a mass-to-volume ratio of Fe3O4@SiO2 nanoparticles to anhydrous ethanol of 1 g: 100~250 mL, add 0.5~2 mL of 3-aminopropyltriethoxysilane (APTES), reflux at 60~100℃ for 4~12 h under nitrogen protection, perform magnetic separation and washing, and vacuum dry at 40~60℃ for 6~12 h to obtain aminated Fe3O4@SiO2 core-shell nanoparticles; (4) Aminated Fe3O4@SiO2 core-shell nanoparticles, glycolide (GA), lactide (LA), and stannous octoate were added to a reaction flask. The mass ratio of Fe3O4@SiO2 core-shell nanoparticles, glycolide, lactide, and stannous octoate was 1:35~60:15~40:0.025~0.25 (GA:LA molar ratio 75:25~90:10). After nitrogen purging, the temperature was raised to 130~150℃, and the reaction was magnetically stirred for 12~24 h. The product was dissolved in chloroform, filtered, and precipitated with excess methanol. This process was repeated three times. The product was then vacuum dried at 40~60℃ for 6~12 h. The grafting rate of the obtained Fe3O4@SiO2-g-PGLA core-shell nanoparticles was approximately 10%~30%.

[0054] In some preferred embodiments, the preparation method of the Fe3O4@SiO2-g-PGA core-shell nanoparticles includes: Fe3O4 nanoparticles were prepared by a solvothermal method, and then SiO2 was coated on the surface of the Fe3O4 nanoparticles by the Stöber method to obtain Fe3O4@SiO2 nanoparticles. Furthermore, the Fe3O4@SiO2 nanoparticles are subjected to surface amination treatment to obtain amination nanoparticles, and then PGA is grafted onto the surface of the amination nanoparticles by ring-opening polymerization to obtain Fe3O4@SiO2-g-PGA core-shell nanoparticles.

[0055] In some preferred embodiments, the preparation method of the Fe3O4@SiO2-g-PGA core-shell nanoparticles includes: (1) FeCl3·6H2O was mixed with NaAc and PEG in ethylene glycol, and Fe3O4 nanoparticles were prepared by solvothermal method. The molar ratio of FeCl3·6H2O to NaAc was 1:2~4, and the mass-volume ratio of PEG (molecular weight 4000~6000) to ethylene glycol was 1g:50~100mL. The reaction pressure was autogenous pressure (closed high pressure vessel), the reaction temperature was 180~220℃, and the reaction time was 8~12 h. After the reaction, the nanoparticles were washed 2~3 times with anhydrous ethanol and deionized water, and vacuum dried at 40~60℃ for 6~12 h. The particle size of the obtained Fe3O4 nanoparticles was about 20~50 nm. (2) Fe3O4 nanoparticles were ultrasonically dispersed in an ethanol / water mixture (volume ratio 4:1), the pH was adjusted to alkaline (pH=8~10), TEOS was slowly added dropwise, and after washing, the Fe3O4@SiO2 core-shell nanoparticles were obtained by vacuum drying. The pH was 8~10, the dropping rate was about 0.05~0.2 mL / min, the reaction time was 12~24 h, the drying temperature was 40~60℃, the drying time was 6~12 h, and the particle size of the obtained Fe3O4@SiO2 core-shell nanoparticles was about 25~65 nm. (3) Disperse Fe3O4@SiO2 nanoparticles in anhydrous ethanol, with a mass-to-volume ratio of Fe3O4@SiO2 nanoparticles to anhydrous ethanol of 1 g: 100~250 mL, add 0.5~2 mL of 3-aminopropyltriethoxysilane (APTES), reflux at 60~100℃ for 4~12 h under nitrogen protection, perform magnetic separation and washing, and vacuum dry at 40~60℃ for 6~12 h to obtain aminated Fe3O4@SiO2 core-shell nanoparticles; (4) Aminated Fe3O4@SiO2 core-shell nanoparticles, glycolide (GA), and stannous octoate were added to a reaction flask. The mass ratio of Fe3O4@SiO2 core-shell nanoparticles, glycolide, and stannous octoate was 1:35~60:0.025~0.25. After nitrogen purging, the temperature was raised to 130~150℃ and the reaction was magnetically stirred for 12~24 h. The product was dissolved in chloroform, filtered, and precipitated with excess methanol. This process was repeated three times. The product was then vacuum dried at 40~60℃ for 6~12 h. The grafting rate of the obtained Fe3O4@SiO2-g-PGA core-shell nanoparticles was approximately 10%~30%.

[0056] Another aspect of the present invention provides a method for preparing the aforementioned magnetically induced core-and-skin absorbable surgical suture, comprising: Poly(PGLA) was melt-blended and granulated with Fe3O4@SiO2-g-PGLA core-shell nanoparticles to obtain a skin layer blend. PGA and Fe3O4@SiO2-g-PGA core-shell nanoparticles were melt-blended and granulated to obtain the core layer blend; The sheath blend and core blend are coaxially melt-spun; after extrusion from the coaxial spinneret, a magnetic field generating device is set below the spinneret. The applied directional gradient magnetic field causes Fe3O4@SiO2-g-PGLA core-shell nanoparticles and Fe3O4@SiO2-g-PGA core-shell nanoparticles to rotate along the fiber axis under the action of the magnetic field and form a chain-like arrangement. They migrate and accumulate towards the sheath surface and towards the interface between the sheath and the core, respectively, and the content gradually increases in the direction away from the core. Then, they are rapidly cooled in a cold water bath to obtain nascent fibers. Furthermore, the nascent fibers are stretched and heat-set to obtain magnetically induced core-skin type absorbable surgical sutures.

[0057] In some preferred embodiments, the preparation method specifically includes: premixing PGLA with Fe3O4@SiO2-g-PGLA core-shell nanoparticles in a high-speed mixer, then adding the mixture to a twin-screw extruder and melt-blending and extruding at 180~210℃ (note that the higher the LA content in PGLA, the lower the melting point of PGLA, and the lower the processing temperature), followed by granulation, and then vacuum drying at 50~80℃ (note that the higher the LA content in PGLA, the lower the crystallinity of PGLA, and the lower the drying temperature) for 12~24h to obtain a skin layer blend; premixing PGA with Fe3O4@SiO2-g-PGA core-shell nanoparticles in a high-speed mixer, then adding the mixture to a twin-screw extruder and melt-blending and extruding at 220~250℃, followed by granulation, and then vacuum drying at 60~90℃ for 12~24h to obtain a core layer blend.

[0058] Furthermore, the melt blending temperature of the skin layer blend is 190~200℃, the vacuum drying temperature is 60~80℃, and the drying time is 16~24h; the melt blending temperature of the core layer blend is 230~240℃, the vacuum drying temperature is 70~90℃, and the drying time is 16~24h.

[0059] Furthermore, the melt blending temperature of the skin layer blend is 194~198℃, the vacuum drying temperature is 70~80℃, and the drying time is 20~24h; the melt blending temperature of the core layer blend is 234~238℃, the vacuum drying temperature is 80~90℃, and the drying time is 20~24h.

[0060] In some preferred embodiments, the preparation method specifically includes: adding the sheath blend and the core blend to a coaxial melt spinning device, wherein the core spinning temperature is 230~260℃, the sheath spinning temperature is 195~230℃, the inner diameter of the core orifice of the coaxial spinneret is 0.2~0.4 mm, and the inner diameter of the outer orifice is 0.5~1.0 mm; setting a magnetic field generating device below the spinneret, the magnetic field generating device including a ring permanent magnet, the magnetic field strength is 0.2~1.0 T, and the magnetic field gradient is 10~100 T / m; after the filament passes through the center of the magnetic ring, it enters a cold water bath for rapid cooling, and is wound up to obtain nascent fibers, the cold water bath temperature is 0~35℃, and the winding speed is 10~200 m / min; the nascent fibers are further subjected to stretching and heat setting treatment, with a stretching temperature of 50~90℃ and a stretching ratio of 3~10 times. After stretching, the fibers are heat set at 70~90℃ for 15~60 min to obtain magnetically induced core-skin type absorbable surgical sutures.

[0061] Furthermore, the core spinning temperature is 238~252℃, the sheath spinning temperature is 205~220℃; the magnetic field strength is 0.4~0.8 T, the magnetic field gradient is 30~80 T / m; the cold water bath temperature is 10~25℃, the winding speed is 40~120 m / min; the drawing temperature is 60~85℃, the drawing ratio is 5~9 times; the heat setting temperature is 75~85℃, and the time is 30~45 min.

[0062] Furthermore, the core spinning temperature is 242~248℃, the sheath spinning temperature is 210~215℃; the magnetic field strength is 0.5~0.7 T, the magnetic field gradient is 45~65 T / m; the cold water bath temperature is 15~20℃, the winding speed is 50~80 m / min; the drawing temperature is 75~82℃, the drawing ratio is 7~8 times; the heat setting temperature is 78~83℃, and the time is 36~42 min.

[0063] In some more specific embodiments, the method for preparing the magnetically induced core-and-skin absorbable surgical suture includes: (1) Preparation of skin layer blend: PGLA and Fe3O4@SiO2-g-PGLA core-shell nanoparticles are melt-blended and granulated; Preparation of core layer blend: PGA and Fe3O4@SiO2-g-PGA core-shell nanoparticles are melt-blended and granulated; (2) Coaxial melt spinning and magnetic field induction: The skin layer blend and core layer blend prepared in step (1) are coaxially melt spun; after being extruded from the coaxial spinneret, a magnetic field generating device is set below the spinneret. The applied directional gradient magnetic field causes Fe3O4@SiO2-g-PGLA core-shell nanoparticles and Fe3O4@SiO2-g-PGA core-shell nanoparticles to rotate along the fiber axis under the action of the magnetic field to form a chain-like arrangement, and migrate and accumulate to the skin layer surface and to the skin layer and core layer interface, respectively, and the content gradually increases in the direction away from the core layer; then it is rapidly cooled in a cold water bath to obtain nascent fibers; (3) Stretching and shaping: The nascent fibers prepared in step (2) are stretched and then heat-shaped to obtain magnetically induced core-skin type absorbable surgical sutures.

[0064] (4) Sterilization and packaging: The core-type absorbable surgical sutures prepared in step (3) are sterilized by ethylene oxide or irradiation and then vacuum-sealed.

[0065] In a preferred embodiment, the core-skin surgical suture has a tensile strength of 4.5~5.6 cN / dtex, a magnetic anisotropy ratio of 1.5~3.0, and a magnetocaloric heating rate of 9.2~16.8℃ / min; after 7 days of in vitro degradation (PBS buffer solution: pH 7.4, 37℃) under magnetic field conditions (30 minutes of alternating magnetic field per day, frequency 300 kHz, field strength 15 mT), the mass loss rate is 6~18%; and after 6 months of dry storage at 25℃, the tensile strength retention rate is 90~98%.

[0066] The technical solution of the present invention will be further described in detail below with reference to several preferred embodiments and accompanying drawings. This embodiment is implemented on the premise of the technical solution of the invention, and provides detailed implementation methods and specific operation processes. However, the protection scope of the present invention is not limited to the following embodiments.

[0067] Unless otherwise specified, the experimental materials used in the examples below can be purchased from conventional biochemical reagent companies.

[0068] Particle morphology and distribution: Observed using transmission electron microscopy or field emission scanning electron microscopy.

[0069] Mechanical properties: The breaking strength was tested using a universal tensile testing machine in accordance with ASTM D2256 standard.

[0070] Magnetic properties: Magnetic anisotropy was tested at room temperature using a vibrating sample magnetometer.

[0071] Magnetothermal effect: An alternating magnetic field generator (frequency 300 kHz, field strength 15 mT) and an infrared thermal imager were used to record temperature changes and heating rates.

[0072] The preparation method of Fe3O4@SiO2-g-PGLA core-shell nanoparticles used in the following examples is as follows: (1) FeCl3·6H2O was mixed with NaAc and PEG in ethylene glycol, and Fe3O4 nanoparticles were prepared by solvothermal method. The molar ratio of FeCl3·6H2O to NaAc was 1:3, and the mass-volume ratio of PEG (molecular weight 4000~6000) to ethylene glycol was 1g:85mL. The reaction pressure was autogenous pressure (closed high pressure vessel), the reaction temperature was 205℃, and the reaction time was 9.5 h. After the reaction was completed, the nanoparticles were washed 33 times with anhydrous ethanol and deionized water, and dried under vacuum at 55℃ for 10 h. The particle size of the Fe3O4 nanoparticles obtained was about 42 nm. (2) Fe3O4 nanoparticles were ultrasonically dispersed in an ethanol / water mixture (volume ratio 4:1), and the pH was adjusted to alkaline (pH=9.5). TEOS was slowly added dropwise, and after washing, the mixture was vacuum dried to obtain Fe3O4@SiO2 core-shell nanoparticles. The pH was 9.5, the dropping rate was approximately 0.14 mL / min, and the reaction time was 20 h. The drying temperature was 55℃, and the drying time was 10 h. The particle size of the obtained Fe3O4@SiO2 core-shell nanoparticles was approximately 55 nm. The SEM image is shown below. Figure 1 As shown; (3) Fe3O4@SiO2 nanoparticles were dispersed in anhydrous ethanol at a mass-to-volume ratio of 1 g to 180 mL. 1.5 mL of 3-aminopropyltriethoxysilane (APTES) was added, and the mixture was refluxed at 85 °C for 10 h under nitrogen protection. After magnetic separation and washing, the mixture was vacuum dried at 55 °C for 10 h to obtain aminated Fe3O4@SiO2 core-shell nanoparticles. (4) Aminated Fe3O4@SiO2 core-shell nanoparticles, glycolide (GA), lactide (LA), and stannous octoate were added to a reaction flask. The mass ratio of Fe3O4@SiO2 core-shell nanoparticles, glycolide, lactide, and stannous octoate was 1:52:28:0.12 (GA:LA molar ratio 80:20). After nitrogen purging, the temperature was raised to 145℃ and the reaction was magnetically stirred for 18 h. The product was dissolved in chloroform, filtered, and precipitated with excess methanol. This process was repeated three times. The product was then vacuum dried at 55℃ for 10 h. The grafting rate of the obtained Fe3O4@SiO2-g-PGLA core-shell nanoparticles was approximately 22%.

[0073] The preparation method of Fe3O4@SiO2-g-PGA core-shell nanoparticles used in the following examples is as follows: (1) FeCl3·6H2O was mixed with NaAc and PEG in ethylene glycol, and Fe3O4 nanoparticles were prepared by solvothermal method. The molar ratio of FeCl3·6H2O to NaAc was 1:3, and the mass-volume ratio of PEG (molecular weight 4000~6000) to ethylene glycol was 1g:85mL. The reaction pressure was autogenous pressure (closed high pressure vessel), the reaction temperature was 205℃, and the reaction time was 9.5 h. After the reaction was completed, the nanoparticles were washed 33 times with anhydrous ethanol and deionized water, and dried under vacuum at 55℃ for 10 h. The particle size of the Fe3O4 nanoparticles obtained was about 42 nm. (2) Fe3O4 nanoparticles were ultrasonically dispersed in an ethanol / water mixture (volume ratio 4:1), the pH was adjusted to alkaline (pH=9.5), TEOS was slowly added dropwise, and after washing, the Fe3O4@SiO2 core-shell nanoparticles were obtained by vacuum drying. The pH was 9.5, the dropping rate was about 0.14 mL / min, the reaction time was 20 h, the drying temperature was 55℃, the drying time was 10 h, and the particle size of the obtained Fe3O4@SiO2 core-shell nanoparticles was about 55 nm. (3) Fe3O4@SiO2 nanoparticles were dispersed in anhydrous ethanol at a mass-to-volume ratio of 1 g to 180 mL. 1.5 mL of 3-aminopropyltriethoxysilane (APTES) was added, and the mixture was refluxed at 85 °C for 10 h under nitrogen protection. After magnetic separation and washing, the mixture was vacuum dried at 55 °C for 10 h to obtain aminated Fe3O4@SiO2 core-shell nanoparticles. (4) Aminated Fe3O4@SiO2 core-shell nanoparticles, glycolide (GA), and stannous octoate were added to a reaction flask. The mass ratio of Fe3O4@SiO2 core-shell nanoparticles, glycolide, and stannous octoate was 1:52:0.12. After nitrogen purging, the temperature was raised to 145℃ and the reaction was magnetically stirred for 18 h. The product was dissolved in chloroform, filtered, and precipitated with excess methanol. This process was repeated three times. The product was then vacuum dried at 55℃ for 10 h. The grafting rate of the obtained Fe3O4@SiO2-g-PGA core-shell nanoparticles was approximately 22%.

[0074] Example 1 This embodiment illustrates the magnetic field-induced skin-core type absorbable surgical suture of the present invention and its preparation method.

[0075] Skin layer blend: PGLA (LA molar content 9%, weight average molecular weight 160,000) and Fe3O4@SiO2-g-PGLA core-shell nanoparticles were premixed in a high-speed mixer at a mass ratio of 100:4. The mixture was then added to a twin-screw extruder and melt-blended at 198℃, extruded and granulated, and vacuum-dried at 80℃ for 20 h to obtain the skin layer blend. The parameters of Fe3O4@SiO2-g-PGLA were: Fe3O4 core particle size 28 nm, SiO2 shell thickness 8 nm, and PGLA grafting rate 18%.

[0076] Core layer blend: PGA (weight average molecular weight 170,000) and Fe3O4@SiO2-g-PGA core-shell nanoparticles were premixed in a high-speed mixer at a mass ratio of 100:1. The mixture was then melt-blended in a twin-screw extruder at 234℃, extruded and granulated, and vacuum-dried at 80℃ for 24 hours to obtain the core layer blend. The parameters of Fe3O4@SiO2-g-PGA were: Fe3O4 core particle size 28 nm, SiO2 shell thickness 8 nm, and PGA grafting rate 18%.

[0077] Coaxial melt spinning and magnetic field induction: The sheath blend and core blend were added separately to a coaxial melt spinning device. The core spinning temperature was 248℃, and the sheath spinning temperature was 215℃. The inner diameter of the core orifice of the coaxial spinneret was 0.4 mm, and the inner diameter of the outer orifice was 1.0 mm. A ring-shaped permanent magnet magnetic field generator was installed 5 cm below the spinneret, with a magnetic field strength of 0.5 T and a magnetic field gradient of 45 T / m. After passing through the center of the magnetic ring, the filament was rapidly cooled in a 15℃ cold water bath, and the winding speed was 50 m / min to obtain nascent fibers.

[0078] Stretching and Heat Setting: Nascent fibers were stretched at 82°C to a stretch ratio of 7, and then heat-set at 83°C for 36 min to obtain magnetically induced core-sheath absorbable surgical sutures. The core-sheath absorbable surgical sutures contained 40 wt% sheath. The stress-strain curves of the prepared surgical sutures before and after 6 months of storage are shown below. Figure 2 As shown.

[0079] Example 2 Skin layer blend: PGLA (LA molar content 10%, weight average molecular weight 170,000) and Fe3O4@SiO2-g-PGLA core-shell nanoparticles were premixed in a high-speed mixer at a mass ratio of 100:5. The mixture was then added to a twin-screw extruder and melt-blended at 195℃, extruded and granulated, and vacuum-dried at 75℃ for 21 h to obtain the skin layer blend. The parameters of Fe3O4@SiO2-g-PGLA were: Fe3O4 core particle size 31 nm, SiO2 shell thickness 10 nm, and PGLA grafting rate 20.3%.

[0080] Core layer blend: PGA (weight average molecular weight 180,000) and Fe3O4@SiO2-g-PGA core-shell nanoparticles were premixed in a high-speed mixer at a mass ratio of 100:1.2. The mixture was then melt-blended in a twin-screw extruder at 236℃, extruded and granulated, and vacuum-dried at 85℃ for 22 hours to obtain the core layer blend. The parameters of Fe3O4@SiO2-g-PGA were: Fe3O4 core particle size 31 nm, SiO2 shell thickness 9 nm, and PGA grafting rate 20%.

[0081] Coaxial melt spinning and magnetic field induction: The sheath blend and core blend were added separately to a coaxial melt spinning device. The core spinning temperature was 245℃, and the sheath spinning temperature was 212℃. The inner diameter of the core orifice of the coaxial spinneret was 0.4 mm, and the inner diameter of the outer orifice was 0.9 mm. A ring-shaped permanent magnet magnetic field generator was installed 5 cm below the spinneret, with a magnetic field strength of 0.6 T and a magnetic field gradient of 50 T / m. After passing through the center of the magnetic ring, the filament was rapidly cooled in a 16℃ cold water bath, and the winding speed was 60 m / min to obtain nascent fibers.

[0082] Stretching and heat setting: The nascent fibers are stretched at 80°C with a stretching ratio of 7.5 times, and then heat-set at 80°C for 40 min to obtain a core-sheath type absorbable surgical suture induced by magnetic field. The core-sheath type absorbable surgical suture has a sheath content of 42wt%.

[0083] Example 3 Skin layer blend: PGLA (LA molar content 11%, weight average molecular weight 180,000) and Fe3O4@SiO2-g-PGLA core-shell nanoparticles were premixed in a high-speed mixer at a mass ratio of 100:6. The mixture was then added to a twin-screw extruder and melt-blended at 194℃, extruded and granulated, and vacuum-dried at 70℃ for 24 h to obtain the skin layer blend. The parameters of Fe3O4@SiO2-g-PGLA were: Fe3O4 core particle size 35 nm, SiO2 shell thickness 10 nm, and PGLA grafting rate 22%.

[0084] Core layer blend: PGA (weight average molecular weight 190,000) and Fe3O4@SiO2-g-PGA core-shell nanoparticles were premixed in a high-speed mixer at a mass ratio of 100:1.4. The mixture was then melt-blended in a twin-screw extruder at 238℃, extruded and granulated, and vacuum-dried at 90℃ for 20 hours to obtain the core layer blend. The parameters of Fe3O4@SiO2-g-PGA were: Fe3O4 core particle size 35 nm, SiO2 shell thickness 10 nm, and PGA grafting rate 22%.

[0085] Coaxial melt spinning and magnetic field induction: The sheath blend and core blend were added separately to a coaxial melt spinning device. The core spinning temperature was 242℃, and the sheath spinning temperature was 210℃. The inner diameter of the core orifice of the coaxial spinneret was 0.4 mm, and the inner diameter of the outer orifice was 0.9 mm. A ring-shaped permanent magnet magnetic field generator was installed 5 cm below the spinneret, with a magnetic field strength of 0.7 T and a magnetic field gradient of 65 T / m. After passing through the center of the magnetic ring, the filament was rapidly cooled in a 20℃ cold water bath, and the winding speed was 80 m / min to obtain nascent fibers.

[0086] Stretching and heat setting: The nascent fibers are stretched at 75°C with a stretching ratio of 8 times, and then heat-set at 78°C for 42 min to obtain a core-sheath type absorbable surgical suture induced by magnetic field. The core-sheath type absorbable surgical suture has a sheath content of 45 wt%.

[0087] Example 4 Skin layer blend: PGLA (LA molar content 7%, weight average molecular weight 140,000) and Fe3O4@SiO2-g-PGLA core-shell nanoparticles were premixed in a high-speed mixer at a mass ratio of 100:3. The mixture was then added to a twin-screw extruder and melt-blended at 200℃, extruded and granulated, and vacuum-dried at 80℃ for 18 hours to obtain the skin layer blend. The parameters of Fe3O4@SiO2-g-PGLA were: Fe3O4 core particle size 25 nm, SiO2 shell thickness 7 nm, and PGLA grafting rate 15%.

[0088] Core layer blend: PGA (weight average molecular weight 160,000) and Fe3O4@SiO2-g-PGA core-shell nanoparticles were premixed in a high-speed mixer at a mass ratio of 100:0.6. The mixture was then melt-blended in a twin-screw extruder at 240℃, extruded and granulated, and vacuum-dried at 78℃ for 24 hours to obtain the core layer blend. The parameters of Fe3O4@SiO2-g-PGA were: Fe3O4 core particle size 25 nm, SiO2 shell thickness 7 nm, and PGA grafting rate 15%.

[0089] Coaxial melt spinning and magnetic field induction: The sheath blend and core blend were added separately to a coaxial melt spinning device. The core spinning temperature was 252℃, and the sheath spinning temperature was 220℃. The inner diameter of the core orifice of the coaxial spinneret was 0.2 mm, and the inner diameter of the outer orifice was 0.6 mm. A ring-shaped permanent magnet magnetic field generator was installed 5 cm below the spinneret, with a magnetic field strength of 0.4 T and a magnetic field gradient of 30 T / m. After passing through the center of the magnetic ring, the filament was rapidly cooled in a 10℃ cold water bath, and the winding speed was 40 m / min to obtain nascent fibers.

[0090] Stretching and heat setting: The nascent fibers are stretched at 85°C with a stretching ratio of 5 times, and then heat-set at 85°C for 30 min to obtain a core-sheath type absorbable surgical suture induced by magnetic field. The core-sheath type absorbable surgical suture has a sheath content of 35wt%.

[0091] Example 5 Skin layer blend: PGLA (LA molar content 13%, weight average molecular weight 200,000) and Fe3O4@SiO2-g-PGLA core-shell nanoparticles were premixed in a high-speed mixer at a mass ratio of 100:8. The mixture was then added to a twin-screw extruder and melt-blended at 190℃, extruded and granulated, and vacuum-dried at 60℃ for 24 h to obtain the skin layer blend. The parameters of Fe3O4@SiO2-g-PGLA were: Fe3O4 core particle size 40 nm, SiO2 shell thickness 12 nm, and PGLA grafting rate 25%.

[0092] Core layer blend: PGA (weight average molecular weight 220,000) and Fe3O4@SiO2-g-PGA core-shell nanoparticles were premixed in a high-speed mixer at a mass ratio of 100:2.2. The mixture was then melt-blended in a twin-screw extruder at 234℃, extruded and granulated, and vacuum-dried at 90℃ for 18 hours to obtain the core layer blend. The parameters of Fe3O4@SiO2-g-PGA were: Fe3O4 core particle size 40 nm, SiO2 shell thickness 12 nm, and PGA grafting rate 25%.

[0093] Coaxial melt spinning and magnetic field induction: The sheath blend and core blend were added separately to a coaxial melt spinning device. The core spinning temperature was 238℃, and the sheath spinning temperature was 205℃. The inner diameter of the core orifice of the coaxial spinneret was 0.4 mm, and the inner diameter of the outer orifice was 1 mm. A ring-shaped permanent magnet magnetic field generator was installed 5 cm below the spinneret, with a magnetic field strength of 0.8 T and a magnetic field gradient of 80 T / m. After passing through the center of the magnetic ring, the filament was rapidly cooled in a 25℃ cold water bath, and the winding speed was 120 m / min to obtain nascent fibers.

[0094] Stretching and heat setting: The nascent fibers are stretched at 60°C with a stretching ratio of 9 times, and then heat-set at 75°C for 45 min to obtain a core-sheath type absorbable surgical suture induced by magnetic field. The core-sheath type absorbable surgical suture has a sheath content of 50 wt%.

[0095] Example 6 Skin layer blend: PGLA (LA molar content 5%, weight average molecular weight 150,000) and Fe3O4@SiO2-g-PGLA core-shell nanoparticles were premixed in a high-speed mixer at a mass ratio of 100:1. The mixture was then added to a twin-screw extruder and melt-blended at 210℃, extruded and granulated, and vacuum-dried at 80℃ for 12 hours to obtain the skin layer blend. The parameters of Fe3O4@SiO2-g-PGLA were: Fe3O4 core particle size 20 nm, SiO2 shell thickness 5 nm, and PGLA grafting rate 10%.

[0096] Core layer blend: PGA (weight average molecular weight 100,000) and Fe3O4@SiO2-g-PGA core-shell nanoparticles were premixed in a high-speed mixer at a mass ratio of 100:0.1. The mixture was then melt-blended in a twin-screw extruder at 250℃, extruded and granulated, and vacuum-dried at 70℃ for 24 hours to obtain the core layer blend. The parameters of Fe3O4@SiO2-g-PGA were: Fe3O4 core particle size 20 nm, SiO2 shell thickness 5 nm, and PGA grafting rate 10%.

[0097] Coaxial melt spinning and magnetic field induction: The sheath blend and core blend are added separately to a coaxial melt spinning device. The core spinning temperature is 260℃, and the sheath spinning temperature is 230℃. The inner diameter of the core orifice of the coaxial spinneret is 0.2 mm, and the inner diameter of the outer orifice is 0.5 mm. A ring-shaped permanent magnet magnetic field generator is set 5 cm below the spinneret, with a magnetic field strength of 0.2 T and a magnetic field gradient of 10 T / m. After the filament passes through the center of the magnetic ring, it is rapidly cooled in a 0℃ cold water bath, and the winding speed is 10 m / min to obtain nascent fibers.

[0098] Stretching and heat setting: The nascent fibers are stretched at 50°C with a stretching ratio of 3, and then heat-set at 70°C for 60 min to obtain a core-sheath type absorbable surgical suture induced by magnetic field. The core-sheath type absorbable surgical suture has a sheath content of 25 wt%.

[0099] Example 7 Skin layer blend: PGLA (LA molar content 25%, weight average molecular weight 80,000) and Fe3O4@SiO2-g-PGLA core-shell nanoparticles were premixed in a high-speed mixer at a mass ratio of 100:10. The mixture was then added to a twin-screw extruder and melt-blended at 180℃, extruded and granulated, and vacuum-dried at 50℃ for 24 h to obtain the skin layer blend. The parameters of Fe3O4@SiO2-g-PGLA were: Fe3O4 core particle size 50 nm, SiO2 shell thickness 15 nm, and PGLA grafting rate 30%.

[0100] Core layer blend: PGA (weight average molecular weight 280,000) and Fe3O4@SiO2-g-PGA core-shell nanoparticles were premixed in a high-speed mixer at a mass ratio of 100:3. The mixture was then melt-blended in a twin-screw extruder at 250℃, extruded and granulated, and vacuum-dried at 90℃ for 16 hours to obtain the core layer blend. The parameters of Fe3O4@SiO2-g-PGA were: Fe3O4 core particle size 50 nm, SiO2 shell thickness 15 nm, and PGA grafting rate 30%.

[0101] Coaxial melt spinning and magnetic field induction: The sheath blend and core blend are added separately to a coaxial melt spinning device. The core spinning temperature is 260℃, and the sheath spinning temperature is 230℃. The inner diameter of the core orifice of the coaxial spinneret is 0.4 mm, and the inner diameter of the outer orifice is 0.7 mm. A ring-shaped permanent magnet magnetic field generator is set 5 cm below the spinneret, with a magnetic field strength of 1 T and a magnetic field gradient of 100 T / m. After the filament passes through the center of the magnetic ring, it is rapidly cooled in a 35℃ cold water bath, and the winding speed is 200 m / min to obtain nascent fibers.

[0102] Stretching and heat setting: The nascent fibers are stretched at 90°C with a stretching ratio of 10, and then heat-set at 90°C for 15 min to obtain a core-sheath type absorbable surgical suture induced by magnetic field. The core-sheath type absorbable surgical suture has a sheath content of 60 wt%.

[0103] Example 8 Skin layer blend: PGLA (LA molar content 12.5%, weight average molecular weight 150,000) and Fe3O4@SiO2-g-PGLA core-shell nanoparticles were premixed in a high-speed mixer at a mass ratio of 100:5. The mixture was then added to a twin-screw extruder and melt-blended at 201℃, extruded and granulated, and vacuum-dried at 72℃ for 21 h to obtain the skin layer blend. The parameters of Fe3O4@SiO2-g-PGLA were: Fe3O4 core particle size 32 nm, SiO2 shell thickness 7.5 nm, and PGLA grafting rate 23%.

[0104] Core layer blend: PGA (weight average molecular weight 210,000) and Fe3O4@SiO2-g-PGA core-shell nanoparticles were premixed in a high-speed mixer at a mass ratio of 100:1. The mixture was then melt-blended in a twin-screw extruder at 245℃, extruded and granulated, and vacuum-dried at 79℃ for 20 hours to obtain the core layer blend. The parameters of Fe3O4@SiO2-g-PGA were: Fe3O4 core particle size 32 nm, SiO2 shell thickness 7.5 nm, and PGA grafting rate 22%.

[0105] Coaxial melt spinning and magnetic field induction: The sheath blend and core blend were added separately to a coaxial melt spinning device. The core spinning temperature was 250℃, and the sheath spinning temperature was 210℃. The inner diameter of the core orifice of the coaxial spinneret was 0.3 mm, and the inner diameter of the outer orifice was 0.9 mm. A ring-shaped permanent magnet magnetic field generator was installed 5 cm below the spinneret, with a magnetic field strength of 0.8 T and a magnetic field gradient of 35 T / m. After passing through the center of the magnetic ring, the filament was rapidly cooled in a 15℃ cold water bath, and the winding speed was 100 m / min to obtain nascent fibers.

[0106] Stretching and heat setting: The nascent fibers are stretched at 70°C with a stretching ratio of 7.75 times, and then heat-set at 75°C for 35 min to obtain a magnetically induced core-sheath absorbable surgical suture. The core-sheath absorbable surgical suture contains 30 wt% sheath.

[0107] Example 9 Skin layer blend: PGLA (LA molar content 8%, weight average molecular weight 100,000) and Fe3O4@SiO2-g-PGLA core-shell nanoparticles were premixed in a high-speed mixer at a mass ratio of 100:3. The mixture was then added to a twin-screw extruder and melt-blended at 205℃, extruded and granulated, and vacuum-dried at 60℃ for 15 h to obtain the skin layer blend. The parameters of Fe3O4@SiO2-g-PGLA were: Fe3O4 core particle size 38 nm, SiO2 shell thickness 10.5 nm, and PGLA grafting rate 23%.

[0108] Core layer blend: PGA (weight average molecular weight 230,000) and Fe3O4@SiO2-g-PGA core-shell nanoparticles were premixed in a high-speed mixer at a mass ratio of 100:2. The mixture was then melt-blended in a twin-screw extruder at 245℃, extruded and granulated, and vacuum-dried at 80℃ for 18 hours to obtain the core layer blend. The parameters of Fe3O4@SiO2-g-PGA were: Fe3O4 core particle size 38 nm, SiO2 shell thickness 10.5 nm, and PGLA grafting rate 23%.

[0109] Coaxial melt spinning and magnetic field induction: The sheath blend and core blend were added separately to a coaxial melt spinning device. The core spinning temperature was 248℃, and the sheath spinning temperature was 212℃. The inner diameter of the core orifice of the coaxial spinneret was 0.2 mm, and the inner diameter of the outer orifice was 0.7 mm. A ring-shaped permanent magnet magnetic field generator was installed 5 cm below the spinneret, with a magnetic field strength of 0.45 T and a magnetic field gradient of 70 T / m. After passing through the center of the magnetic ring, the filament was rapidly cooled in a 12℃ cold water bath, and the winding speed was 90 m / min to obtain nascent fibers.

[0110] Stretching and heat setting: The nascent fibers are stretched at 80°C with a stretching ratio of 7.5 times, and then heat-set at 82°C for 30 min to obtain magnetically induced core-sheath absorbable surgical sutures. The core-sheath absorbable surgical sutures contain 40 wt% sheath.

[0111] Example 10 Skin layer blend: PGLA (LA molar content 11.5%, weight average molecular weight 172,000) and Fe3O4@SiO2-g-PGLA core-shell nanoparticles were premixed in a high-speed mixer at a mass ratio of 100:5.5. The mixture was then added to a twin-screw extruder and melt-blended at 215℃, extruded and granulated, and vacuum-dried at 67℃ for 19 h to obtain the skin layer blend. The parameters of Fe3O4@SiO2-g-PGLA were: Fe3O4 core particle size 32 nm, SiO2 shell thickness 10 nm, and PGLA grafting rate 20%.

[0112] Core-layer blend: PGA (weight-average molecular weight 215,000) and Fe3O4@SiO2-g-PGA core-shell nanoparticles were premixed in a high-speed mixer at a mass ratio of 100:1.5. The mixture was then melt-blended in a twin-screw extruder at 245℃, extruded and granulated, and vacuum-dried at 88℃ for 19 h to obtain the core-layer blend. The parameters of Fe3O4@SiO2-g-PGA were: Fe3O4 core particle size 32 nm, SiO2 shell thickness 10 nm, and PGLA grafting rate 20%.

[0113] Coaxial melt spinning and magnetic field induction: The sheath blend and core blend were added separately to a coaxial melt spinning device. The core spinning temperature was 250℃, and the sheath spinning temperature was 218℃. The inner diameter of the core orifice of the coaxial spinneret was 0.3 mm, and the inner diameter of the outer orifice was 0.8 mm. A ring-shaped permanent magnet magnetic field generator was installed 5 cm below the spinneret, with a magnetic field strength of 0.56 T and a magnetic field gradient of 75 T / m. After passing through the center of the magnetic ring, the filament was rapidly cooled in a 17℃ cold water bath, and the winding speed was 70 m / min to obtain nascent fibers.

[0114] Stretching and heat setting: The nascent fibers are stretched at 78°C with a stretching ratio of 7.25 times, and then heat-set at 82°C for 36 min to obtain a magnetically induced core-sheath type absorbable surgical suture. The core-sheath type absorbable surgical suture has a sheath content of 46 wt%.

[0115] Example 11 Skin layer blend: PGLA (LA molar content 20%, weight average molecular weight 140,000) and Fe3O4@SiO2-g-PGLA core-shell nanoparticles were premixed in a high-speed mixer at a mass ratio of 100:3.5. The mixture was then added to a twin-screw extruder and melt-blended at 210℃, extruded and granulated, and vacuum-dried at 62℃ for 18 hours to obtain the skin layer blend. The parameters of Fe3O4@SiO2-g-PGLA were: Fe3O4 core particle size 38 nm, SiO2 shell thickness 11.5 nm, and PGLA grafting rate 27%.

[0116] Core layer blend: PGA (weight average molecular weight 160,000) and Fe3O4@SiO2-g-PGA core-shell nanoparticles were premixed in a high-speed mixer at a mass ratio of 100:1.3. The mixture was then melt-blended in a twin-screw extruder at 230℃, extruded and granulated, and vacuum-dried at 75℃ for 19 h to obtain the core layer blend. The parameters of Fe3O4@SiO2-g-PGA were: Fe3O4 core particle size 38 nm, SiO2 shell thickness 11.5 nm, and PGLA grafting rate 27%.

[0117] Coaxial melt spinning and magnetic field induction: The sheath blend and core blend were added separately to a coaxial melt spinning device. The core spinning temperature was 242℃, and the sheath spinning temperature was 220℃. The inner diameter of the core orifice of the coaxial spinneret was 0.3 mm, and the inner diameter of the outer orifice was 0.8 mm. A ring-shaped permanent magnet magnetic field generator was installed 5 cm below the spinneret, with a magnetic field strength of 0.65 T and a magnetic field gradient of 40 T / m. After passing through the center of the magnetic ring, the filament was rapidly cooled in a 15℃ cold water bath, and the winding speed was 75 m / min to obtain nascent fibers.

[0118] Stretching and heat setting: The nascent fibers are stretched at 82°C with a stretching ratio of 8 times, and then heat-set at 84°C for 33 minutes to obtain a magnetically induced core-sheath type absorbable surgical suture. The core-sheath type absorbable surgical suture has a sheath content of 45wt%.

[0119] Example 12 Skin layer blend: PGLA (LA molar content 10%, weight average molecular weight 180,000) and Fe3O4@SiO2-g-PGLA core-shell nanoparticles were premixed in a high-speed mixer at a mass ratio of 100:5. The mixture was then added to a twin-screw extruder and melt-blended at 205℃, extruded and granulated, and vacuum-dried at 65℃ for 20 h to obtain the skin layer blend. The parameters of Fe3O4@SiO2-g-PGLA were: Fe3O4 core particle size 35 nm, SiO2 shell thickness 10 nm, and PGLA grafting rate 22%.

[0120] Core layer blend: PGA (weight average molecular weight 180,000) and Fe3O4@SiO2-g-PGA core-shell nanoparticles were premixed in a high-speed mixer at a mass ratio of 100:1.2. The mixture was then melt-blended in a twin-screw extruder at 235℃, extruded and granulated, and vacuum-dried at 78℃ for 18 hours to obtain the core layer blend. The parameters of Fe3O4@SiO2-g-PGA were: Fe3O4 core particle size 35 nm, SiO2 shell thickness 10 nm, and PGA grafting rate 22%.

[0121] Coaxial melt spinning and magnetic field induction: The sheath blend and core blend were added separately to a coaxial melt spinning device. The core spinning temperature was 245℃, and the sheath spinning temperature was 215℃. The inner diameter of the core orifice of the coaxial spinneret was 0.3 mm, and the inner diameter of the outer orifice was 0.7 mm. A ring-shaped permanent magnet magnetic field generator was installed 5 cm below the spinneret, with a magnetic field strength of 0.6 T and a magnetic field gradient of 36 T / m. After passing through the center of the magnetic ring, the filament was rapidly cooled in a 15℃ cold water bath, and the winding speed was 60 m / min to obtain nascent fibers.

[0122] Stretching and heat setting: The nascent fibers are stretched at 89°C with a stretching ratio of 7.5 times, and then heat-set at 80°C for 36 min to obtain a magnetically induced core-sheath absorbable surgical suture. The core-sheath absorbable surgical suture has a sheath content of 48 wt%.

[0123] Comparative Example 1 (No SiO2 shell, exposed Fe3O4) The method was followed in Example 1, except that Fe3O4@SiO2-g-PGLA and Fe3O4@SiO2-g-PGA were replaced with uncoated Fe3O4-g-PGLA and Fe3O4-g-PGA (bare Fe3O4 core, directly grafted polymer), respectively. All other conditions were the same as in Example 1.

[0124] The suture prepared in this comparative example has a breaking strength of 4.6 cN / dtex, a magnetic anisotropy ratio of 2.7:1, and a magnetocaloric heating rate of 14.1℃ / min. After 7 days of in vitro degradation (PBS buffer solution: pH 7.4, 37℃) under magnetic field conditions (30 minutes of alternating magnetic field per day, frequency 300 kHz, field strength 15 mT), the mass loss rate was 24.6%, and the breaking strength retention rate was 72% after 6 months of dry storage at 25℃.

[0125] Comparative Example 2 (without magnetic field induction) The method is the same as in Example 1, except that no external magnetic field is applied during the coaxial melt spinning process (magnetic field strength 0T). All other conditions are the same as in Example 1.

[0126] The suture prepared in this comparative example has a breaking strength of 4.3 cN / dtex, a magnetic anisotropy ratio of 1.1:1 (nearly isotropic), and a magnetocaloric heating rate of 8.5℃ / min. After 7 days of in vitro degradation (PBS buffer solution: pH 7.4, 37℃) under magnetic field conditions (30 minutes of alternating magnetic field per day, frequency 300 kHz, field strength 15 mT), the mass loss rate was 5.2%. After 6 months of dry storage at 25℃, the breaking strength retention rate was 92%, with no obvious particle migration and enrichment phenomenon, and particles were randomly distributed in the cortex and core.

[0127] Comparative Example 3 (Particle-ungrafted polymer) The method was the same as in Example 1, except that ungrafted Fe3O4@SiO2 (without PGLA or PGA grafted layers) was added to both the cortex and core layers. All other conditions were the same as in Example 1.

[0128] The suture prepared in this comparative example has a breaking strength of 2.6 cN / dtex, a magnetic anisotropy ratio of 2.3:1, and a magnetocaloric heating rate of 10.5℃ / min. After 7 days of in vitro degradation (PBS buffer solution: pH 7.4, 37℃) under magnetic field conditions (30 minutes of alternating magnetic field per day, frequency 300 kHz, field strength 15 mT), the mass loss rate was 13.2%, and the breaking strength retention rate was 95% after 6 months of dry storage at 25℃. The nanoparticles showed significant aggregation, resulting in a high breakage rate during spinning.

[0129] Comparative Example 4 (single-layer structure, without core) The method is the same as in Example 1, except that a single-layer fiber structure (non-core type) is used, and the sheath blend of Example 1 is melt-spun separately (without core layer or core particles), while the other spinning and magnetic field conditions are the same.

[0130] The suture prepared in this comparative example has a breaking strength of 3.5 cN / dtex, a magnetic anisotropy ratio of 3.0:1, and a magnetocaloric heating rate of 15.2℃ / min. After 7 days of in vitro degradation (PBS buffer solution: pH 7.4, 37℃) under magnetic field conditions (30 minutes of alternating magnetic field per day, frequency 300 kHz, field strength 15 mT), the mass loss rate was 17.2%, and the breaking strength retention rate was 92% after 6 months of dry storage at 25℃.

[0131] Comparative Example 5 (core layer contains no magnetic particles) The method was the same as in Example 1, except that Fe3O4@SiO2-g-PGA (i.e., pure PGA) was not added to the core layer blend, and only the skin layer contained magnetic particles. All other conditions were the same as in Example 1.

[0132] The suture prepared in this comparative example has a breaking strength of 5.1 cN / dtex, a magnetic anisotropy ratio of 3.2:1, and a magnetocaloric heating rate of 10.3℃ / min (heat generated solely by cortical particles). After 7 days of in vitro degradation (PBS buffer solution: pH 7.4, 37℃) under magnetic field conditions (30 minutes of alternating magnetic field per day, frequency 300kHz, field strength 15 mT), the mass loss rate was 11.2%. After 6 months of dry storage at 25℃, the breaking strength retention rate was 95%. The core layer showed no magnetic enhancement, and the magnetocaloric efficiency was slightly lower.

[0133] Comparative Example 6 (Cortex without magnetic particles) The method was the same as in Example 1, except that Fe3O4@SiO2-g-PGLA (i.e., pure PGLA) was not added to the skin layer blend, and only the core layer contained magnetic particles. All other conditions were the same as in Example 1.

[0134] The suture prepared in this comparative example has a breaking strength of 4.9 cN / dtex, a magnetic anisotropy ratio of 2.0:1, and a magnetocaloric heating rate of 11.4℃ / min (heat generated solely by core particles). After 7 days of in vitro degradation (PBS buffer solution: pH 7.4, 37℃) under magnetic field conditions (30 minutes of alternating magnetic field per day, frequency 300kHz, field strength 15 mT), the mass loss rate was 13.4%, and the breaking strength retention rate was 92% after 6 months of dry storage at 25℃.

[0135] Comparative Example 7 (no rapid cooling, natural cooling) The method is the same as in Example 1, except that a cold water bath is not used; the filaments are allowed to cool and solidify naturally in the air (at an environment of approximately 25°C).

[0136] The suture prepared in this comparative example had a breaking strength of 3.8 cN / dtex, a magnetic anisotropy ratio of 2.5:1, and a magnetocaloric heating rate of 13.3℃ / min. After 7 days of in vitro degradation (PBS buffer solution: pH 7.4, 37℃) under magnetic field conditions (30 minutes of alternating magnetic field per day, frequency 300 kHz, field strength 15 mT), the mass loss rate was 14.5%, and the breaking strength retention rate was 88% after 6 months of dry storage at 25℃. Due to the slow cooling rate, the magnetic field-induced particle arrangement was slightly loose, and the degree of polymer orientation crystallization was also low.

[0137] Comparative Example 8 (excessive particle content in the cortex blend) The method is the same as in Example 1, except that the mass ratio of PGLA to Fe3O4@SiO2-g-PGLA in the skin layer blend is 100:20.

[0138] This comparative example is not spinnable and cannot be used to produce sutures.

[0139] Comparative Example 9 (excessive particle content in the core layer blend) The method is the same as in Example 1, except that the mass ratio of PGA to Fe3O4@SiO2-g-PGA in the core layer blend is 100:8.

[0140] This comparative example is not spinnable and cannot be used to produce sutures.

[0141] Comparative Example 10 (Particle content in the cortex blend is too low) The method was the same as in Example 1, except that the mass ratio of PGLA to Fe3O4@SiO2-g-PGLA in the skin layer blend was 100:0.5. All other conditions were the same as in Example 1.

[0142] The suture prepared in this comparative example had a breaking strength of 5.4 cN / dtex, a magnetic anisotropy ratio of 1.8:1, and a magnetocaloric heating rate of 12.3℃ / min. After 7 days of in vitro degradation (PBS buffer solution: pH 7.4, 37℃) under magnetic field conditions (30 minutes of alternating magnetic field per day, frequency 300 kHz, field strength 15 mT), the mass loss rate was 13.2%. After 6 months of dry storage at 25℃, the breaking strength retention rate was 95%. The low content of cortical particles resulted in a lack of magnetic enhancement and a slightly lower magnetocaloric efficiency.

[0143] Comparative Example 11 (Particle content in the core layer blend is too low) The method was the same as in Example 1, except that the mass ratio of PGA to Fe3O4@SiO2-g-PGA in the core layer blend was 100:0.05. All other conditions were the same as in Example 1.

[0144] The suture prepared in this comparative example had a breaking strength of 5.8 cN / dtex, a magnetic anisotropy ratio of 3.3:1, and a magnetocaloric heating rate of 16.2℃ / min. After 7 days of in vitro degradation (PBS buffer solution: pH 7.4, 37℃) under magnetic field conditions (30 minutes of alternating magnetic field per day, frequency 300 kHz, field strength 15 mT), the mass loss rate was 12.6%. After 6 months of dry storage at 25℃, the breaking strength retention rate was 96%. The core particle content was too low, resulting in a lack of magnetic enhancement and slightly lower magnetocaloric efficiency.

[0145] The process parameters used in Examples 1-12 are summarized in Table 1.

[0146] Table 1 The characterization data of Examples 1-12 and Comparative Examples 1-11 are shown in Table 2: Table 2 In addition, the inventors of this case also conducted experiments with other raw materials, process operations, and process conditions described in this specification, referring to the aforementioned embodiments, and obtained relatively ideal results in all cases.

[0147] It should be understood that the technical solutions of the present invention are not limited to the specific embodiments described above. Any technical modifications made to the technical solutions of the present invention without departing from the spirit and scope of the claims are within the scope of protection of the present invention.

Claims

1. A magnetic field-induced skin-core type absorbable surgical suture, characterized in that: The core-and-skin type absorbable surgical suture includes a skin layer and a core layer. The skin layer includes poly(ethylene lactide) and Fe3O4@SiO2-g-PGLA core-shell nanoparticles. The Fe3O4@SiO2-g-PGLA core-shell nanoparticles include Fe3O4 as the core, SiO2 as the intermediate shell, and poly(ethylene lactide) as the surface graft layer. The surface graft layer is grafted onto the surface of the SiO2 shell through ring-opening polymerization or chemical coupling. The Fe3O4@SiO2-g-PGLA core-shell nanoparticles are arranged in a chain-like orientation along the suture axis in the skin layer and are enriched towards the skin surface, with the content gradually increasing in the direction away from the core layer. The core layer comprises polyethylene glycol (PEG) and Fe3O4@SiO2-g-PGA core-shell nanoparticles. The Fe3O4@SiO2-g-PGA core-shell nanoparticles comprise Fe3O4 as the core, a SiO2 shell as the intermediate shell, and PGA as the surface graft layer. The surface graft layer is grafted onto the surface of the SiO2 shell through ring-opening polymerization or chemical coupling. The Fe3O4@SiO2-g-PGA core-shell nanoparticles are arranged in a chain-like orientation along the surgical suture axis in the core layer, and are enriched at the interface between the skin and the core layer. The content gradually increases in the core layer in the direction away from the core layer.

2. The core-type absorbable surgical suture according to claim 1, characterized in that: The mass ratio of poly(lactic acid) to Fe3O4@SiO2-g-PGLA core-shell nanoparticles in the skin layer is 100:1~10, preferably 100:3~8, and more preferably 100:4~6; And / or, the mass ratio of PGA to Fe3O4@SiO2-g-PGA core-shell nanoparticles in the core layer is 100:0.1~3, preferably 100:0.6~2.2, and particularly preferably 100:1.0~1.4; And / or, the content of the dermis in the core-type absorbable surgical suture is 25-60 wt%, preferably 35-50 wt%, and particularly preferably 40-45 wt%.

3. The core-type absorbable surgical suture according to claim 1, characterized in that: The weight-average molecular weight of the poly(ethylene glycol) lactide is 80,000 to 250,000, preferably 140,000 to 200,000, and most preferably 160,000 to 180,000. And / or, the molar content of LA in the poly(lactic-coated lactide) is 5-15%, preferably 7-13%, and particularly preferably 9-11%; And / or, the weight-average molecular weight of the polyglycolic acid is 100,000 to 280,000, preferably 160,000 to 220,000, and particularly preferably 170,000 to 190,000.

4. The core-type absorbable surgical suture according to claim 1, characterized in that: The Fe3O4 core-shell nanoparticles described above have a particle size of 20-50 nm, preferably 25-40 nm, and more preferably 28-35 nm. And / or, the thickness of the SiO2 shell in the Fe3O4@SiO2-g-PGLA core-shell nanoparticles is 5-15 nm, preferably 7-12 nm, and particularly preferably 8-10 nm; And / or, the grafting rate of poly(lactic acid) as the surface grafting layer in the Fe3O4@SiO2-g-PGLA core-shell nanoparticles is 10-30 wt%, preferably 15-25 wt%, and particularly preferably 18-22 wt%; And / or, the particle size of Fe3O4 serving as the core in the Fe3O4@SiO2-g-PGA core-shell nanoparticles is 20-50 nm, preferably 25-40 nm, and particularly preferably 28-35 nm; And / or, the thickness of the SiO2 shell in the Fe3O4@SiO2-g-PGA core-shell nanoparticles is 5-15 nm, preferably 7-12 nm, and particularly preferably 8-10 nm; And / or, the grafting rate of polyglycolic acid as the surface grafting layer in the Fe3O4@SiO2-g-PGA core-shell nanoparticles is 10-30 wt%, preferably 15-25 wt%, and particularly preferably 18-22 wt%.

5. The core-type absorbable surgical suture according to claim 1, characterized in that: The surgical suture has a higher magnetic susceptibility along the axial direction than that perpendicular to the axial direction, and the magnetic anisotropy ratio is 1.5~3.0 : 1, preferably 2.0~3.0 : 1, and particularly preferably 2.7~3.0 :

1.

6. The core-type absorbable surgical suture according to claim 1, characterized in that, The preparation method of the Fe3O4@SiO2-g-PGLA core-shell nanoparticles includes: Fe3O4 nanoparticles were prepared by a solvothermal method, and then SiO2 was coated on the surface of the Fe3O4 nanoparticles by the Stöber method to obtain Fe3O4@SiO2 nanoparticles. Furthermore, the Fe3O4@SiO2 nanoparticles are subjected to surface amination treatment to obtain amination nanoparticles, and then PGLA is grafted onto the surface of the amination nanoparticles by ring-opening polymerization to obtain Fe3O4@SiO2-g-PGLA core-shell nanoparticles. And / or, the preparation method of the Fe3O4@SiO2-g-PGA core-shell nanoparticles includes: Fe3O4 nanoparticles were prepared by a solvothermal method, and then SiO2 was coated on the surface of the Fe3O4 nanoparticles by the Stöber method to obtain Fe3O4@SiO2 nanoparticles. Furthermore, the Fe3O4@SiO2 nanoparticles were subjected to surface amination treatment to obtain amination-treated nanoparticles. Subsequently, PGA was grafted onto the surface of the amination-treated nanoparticles via ring-opening polymerization, thereby preparing Fe3O4@SiO2-g-PGA core-shell nanoparticles.

7. The method for preparing the magnetically induced core-and-skin absorbable surgical suture as described in any one of claims 1-6, characterized in that, include: Poly(ethylene lactide) and Fe3O4@SiO2-g-PGLA core-shell nanoparticles were melt-blended and granulated to obtain a skin layer blend. Polyglycolic acid was melt-blended and granulated with Fe3O4@SiO2-g-PGA core-shell nanoparticles to obtain a core layer blend. The sheath blend and core blend are coaxially melt-spun; after extrusion from the coaxial spinneret, a magnetic field generating device is set below the spinneret. The applied directional gradient magnetic field causes Fe3O4@SiO2-g-PGLA core-shell nanoparticles and Fe3O4@SiO2-g-PGA core-shell nanoparticles to rotate along the fiber axis under the action of the magnetic field and form a chain-like arrangement. They migrate and accumulate towards the sheath surface and towards the interface between the sheath and the core, respectively, and the content gradually increases in the direction away from the core. Then, they are rapidly cooled in a cold water bath to obtain nascent fibers. Furthermore, the nascent fibers are stretched and heat-set to obtain magnetically induced core-skin type absorbable surgical sutures.

8. The preparation method according to claim 7, characterized in that, Specifically, it includes: Poly(ethylene lactide) and Fe3O4@SiO2-g-PGLA core-shell nanoparticles were premixed in a high-speed mixer, then added to a twin-screw extruder and melt-blended at 180-210℃, extruded and granulated, and then vacuum-dried at 50-80℃ for 12-24h to obtain a skin layer blend. Polyglycolic acid and Fe3O4@SiO2-g-PGA core-shell nanoparticles were premixed in a high-speed mixer, then added to a twin-screw extruder and melt-blended at 220~250℃, extruded and granulated, and then vacuum dried at 60~90℃ for 12~24h to obtain the core layer blend.

9. The preparation method according to claim 7, characterized in that, Specifically, it includes: The sheath blend and core blend are respectively added to a coaxial melt spinning device. The core spinning temperature is 230-260℃, and the sheath spinning temperature is 195-230℃. The inner diameter of the core orifice of the coaxial spinneret is 0.2-0.4 mm, and the inner diameter of the outer orifice is 0.5-1.0 mm. A magnetic field generating device is set below the spinneret. The magnetic field generating device includes a ring-shaped permanent magnet with a magnetic field strength of 0.2~1.0 T and a magnetic field gradient of 10~100 T / m. After the filament passes through the center of the magnetic ring, it enters a cold water bath for rapid cooling and is wound up to obtain nascent fibers. The cold water bath temperature is 0~35℃, and the winding speed is 10~200. m / min; the nascent fibers are further subjected to stretching and heat setting treatment, with a stretching temperature of 50~90℃ and a stretching ratio of 3~10 times. After stretching, the fibers are heat set at 70~90℃ for 15~60 min to obtain magnetically induced core-skin type absorbable surgical sutures.

10. The preparation method according to claim 9, characterized in that: The core spinning temperature is 238~252℃, and the sheath spinning temperature is 205~220℃; the magnetic field strength is 0.4-0.8 T, the magnetic field gradient is 30-80 T / m, the cold water bath temperature is 10~25℃, the winding speed is 40~120 m / min; the drawing temperature is 60~85℃, the drawing ratio is 5~9 times; the heat setting temperature is 75~85℃, and the time is 30~45 min.

Citation Information

Patent Citations

  • Magnetic field-induced assisted spinning device and its production method for conductive / magnetic chemical fibers

    CN104963018B

  • Preparation method of magnetic composite fiber, magnetic composite fiber and application of magnetic composite fiber

    CN115400256A

  • Drug-loaded nanofiber membrane / polylactic acid absorbable surgical suture and preparation method thereof

    CN116808278B

  • Surgical suture and preparation method thereof

    CN117531037A

  • Drug / electricity synergistic antibacterial and healing promoting suture line and preparation method thereof

    CN118949108A